First report of a Copitarsia species (Lepidoptera. Noctuidae) damaging soybean crops, with identification key to most common pest species - San Blas, Diego German (2022)
The genus Copitarsia Hampson (Lepidoptera. Noctuidae) includes agricultural pests of at least 48 crop plants and they are distributed from Mexico to southern South America. In South America, from Venezuela to Chile and Argentina, Copitarsia incommoda (Walker) is one of the most economic important species of the genus. In this work, we record for the first time for Copitarsia, and specifically for C. incommoda, larvae feeding on soybean leaves and beans. Also, this species is recorded for the first time for Argentina, feeding on lucerne crops. Finally, we provide a larval identification key for most common noctuoids soybean pests of South America, including C. incommoda. This will be helpful for identify this species in soybean crops without the need of larvae rearing.